Penyuluhan Hipertensi Berbasis Posyandu Lansia dalam Meningkatkan Pengetahuan Melalui Pendekatan Partisipatif di Dusun Krikilan, Ngaglik, Sleman - Aninda Nuraini; Theodorus Indarto (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2024)
Hypertension is a major non-communicable disease with a high prevalence among older adults, requiring community-based promotive and preventive interventions. Limited knowledge regarding risk factors, dietary management, and physical activity remains a key barrier to effective hypertension control among the elderly. This community service activity aimed to improve elderly knowledge through health education at the elderly integrated service post (Posyandu Lansia) in Dusun Krikilan, within the working area of Ngaglik II Primary Health Center. A participatory educational approach with a one-group pretest–posttest design was employed. The activity was conducted on November 3, 2023, involving 20 elderly participants. The intervention included interactive lectures, discussions, question-and-answer sessions, and leaflet-based education. The results demonstrated an increase in participants’ knowledge based on pretest–posttest score comparison, with more than 70% of participants showing improvement. Additionally, over 50% of participants actively engaged in the discussion sessions. These findings indicate that community-based health education is effective in improving elderly understanding of hypertension. The activity also reinforces the role of elderly posyandu as a platform for health education. Continuous implementation is recommended to support long-term behavioral changes in hypertension management.